From Struggle to Recognition: Strengthening the Existence of the Lapandewa Kabelengkao Indigenous Legal Community, South Buton Regency - Nur Intan; Jumiati Ukkas; Heryanti Heryanti; Fermas Fermas (Journal of Law, Social Science and Management, 2025)
Background: Strengthening indigenous peoples into indigenous peoples into indigenous law communities requires comprehensive efforts that involve recognition, protection, and empowerment. This includes strengthening customary institutions, increasing community participation, integrating customary law into the national legal system, and aligning customary law with the times. Objectives: to examine the development of customary law in the current era of globalization using normative juridical methods. Methods: This study uses a normative legal research method, which means that the author conducts a process to find a rule of law, legal principles, and legal doctrines to answer legal problems and produce an argument, as well as new theories or concepts as prescriptions in solving problems Results: the national cultural identity and customary land rights of indigenous peoples are respected and protected as long as they do not conflict with the principles of state law. Conclusion: the recognition of the existence of the community in the Lapandewa Kabelengkao should be accompanied by strengthening regulations. So this can result in the recognition of their existence. The requirements to become a customary law society have actually been met.